The Effect of Marketing Mix of Educational Services and Image Formation on Student Decisions to Choose Private Universities in Bandung - Heni Sri Lestari; Miswan Miswan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
This study aims to measure and analyze the factors in the service marketing mix and image formation, namely reputation and credibility that can influence consumer selection decisions. More specifically, this research takes the context of educational services, with students as consumers who consider the College of Administrative Sciences (STIA) Bandung as their preferred private university. This research was conducted with quantitative methods on 113 STIA Bandung students who were determined by simple random sampling method. The data were obtained from observations, documentation studies, distributing questionnaires to respondents, as well as interviews with leaders and staff on campus. The results of this study indicate that the three variables, namely marketing mix, reputation, and credibility have a positive and significant impact on the decision to choose a university in Bandung. Thus, universities need to apply these three variables as a strategy to attract students' interest in choosing universities.